Ramayana Ballet Performance's Allure at Purawisata Yogyakarta - Endang Caturwati; Een Herdiani; Suzen HR Lumban Tobing (Institut Seni Indonesia Denpasar, 2022)
Indonesia is known for its Wayang Orang performances, especially in the areas of Surakarta, Yogyakarta, Semarang, Jakarta, and Bali. Among the Wayang Orang performances, there was a group that switched to ballet performances, which later became known as the Ramaya Ballet Purawisata Yogyakarta. The purpose of this study is to dissect more deeply the Ramayana Ballet Performance and the extent of its influence on people's lives. Purawisata's Ramayana Ballet, shown in full every night from 20.00–21.30 WIB since 1976 until 2001, won the 'Guinness Book of Records' (MURI) for its consistency in performing cultural performances for 29 years continuously. Consistency in maintaining the noble values of culture continues until August 10, 2021, when Purawisata's Ramayana Ballet is 45 years old. The method used in this research is a qualitative, descriptive analysis method that explores and understands the meaning of a number of individuals or groups of arts being studied. The results of the study show that the innovation strategies offered to the audience are: (1) Special Package Ramayana Performances; (2) Ramayana Edukasi; and (3) Regular Ramayana, so the Ramayana Ballet show still exists today. Even at regular shows, tickets with seating for 600 people are always full.